Effect of Jasmonic Acid on Physiological and Phytochemical Attributes and Antioxidant Enzymes Activity in Safflower (Carthamus tinctorius L.) under Water Deficient - R Khademian; M Ghorbani Nohooji; B Asghari (Institue of Medicinal Plants, ACECR, 2019)
Background: Safflower (Carthamus tinctorius L.), is an important medicinal plant of Asteraceae family, which is a rich source of pharmaceutically active compounds including phenols, flavonoids and fatty acids. In traditional medicine this plant has been used as an herbal medicine to treat various diseases. Objective: The aim of this study was to evaluate the role of jasmonic acid to protect safflower against drought damages. Method: The greenhouse experiment was conducted as a factorial experiment in a completely randomized design with three replications. The first factor was irrigation regime, which was applied at four levels: field capacity (FC), 0.8 FC, 0.6 FC and 0.4 FC. The second factor was application of jasmonic acid in three concentrations (0, 0.5 and 1 mM). Results: According to the obtained results activities of antioxidant enzymes including catalase, superoxide dismutase and glutathione peroxidase, and also the amount of compounds like abscisic acid, proline, malondealdehyde, protein, phenols and flavonoids contents were significantly increased in safflower by enhancement of water stress. Conversely, relative leaf water content (RWC) exhibited a significant decrease due to water deficit. According to the obtained results, application of jasmonic acid can mitigate the adverse effect of drought stress on the mentioned attributes. Also, the amount of main fatty acids in the oil were significantly changed due to water deficient. Conclusion: The results illustrated that jasmonic acid has an important role in increasing safflower ability to cope against drought stress through improvement of antioxidant enzymes activities and enhancement of secondary methabolites.